Effect of Vagus Nerve Stimulation on Blood Inflammatory Markers in Children with Drug-Resistant Epilepsy: A Pilot Study - Valentina Baro; Maria Vittoria Bonavina; Francesco Saettini; Giovanna D'Amico; Andrea Trezza; Luca Denaro; Daniele Grioni; Andrea Landi (MDPI AG, 2022)
Background: Since one of the suggested mechanisms of action of VNS on epilepsy is the reduction of central inflammation, we carried out a comprehensive analysis of blood inflammatory markers in children considered for VNS surgery. Materials and methods: Five pediatric patients were studied. An extensive analysis of blood inflammatory markers was performed before surgery (T0) and six weeks after VNS implantation (T1). An epileptological outcome was obtained according to the McHugh score. Results: The variations of IgA, IgE, IgG, CD19, and PTX3 displayed a tendency toward a positive statistical correlation between T0 and T1. According to McHugh score, the patients were divided into Group 1 (i.e., Class I) and Group 2 (i.e., Classes II and III). IL-1β and PTX-3 tended to decrease more in Group 1, while TNF-α decreased in Group 2 (−56.65%) and slightly increased (+3.61%) in Group 1 at T1 without statistical correlation. Conclusions: The variation of IL-1β and PTX-3 seem to be related to a better outcome; thus, they do not reach statistical significance. A larger series of patients is needed to determine whether biochemical changes could relay with the clinical improvement of epilepsy.